The Climate Threat. Crisis for Democracy? - Naustdalslid, Jon. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
A key point in the book is the need to focus more seriously at the energy problem as the real problem behind global warming. The failure of global climate policies to reduce CO2 emissions and halt climate change has led an increasing number of scientist and activists to lose confidence in democracy's ability to handle climate change and led them to look to more authoritarian measures to meet the problem. The book documents these trends, also from a historical perspective, criticize them and sketches more democratic alternatives.
PART I : The climate threat and democracy -- Chapter 1 The point of departure -- Chapter 2 The climate problem and climate policy -- Part II Antidemocratic threats -- Chapter 3 The antidemocratic heritage and the dream about "Eco dictatorship" -- Chapter 4 The current climate debate and the threat to democracy -- Chapter 5 Popular climate uproar and the undermining of democracy -- Chapter 6 The "non-political" solution of the climate problem -- PART III DEMOCRATIC ALTERNATIVES -- Chapter 7 A wicked problem -- Chapter 8 Contributions to democratic answers to the climate problem -- Chapter 9 The dream about Paradise.
Keywords: Climatology; Environmental Law; Political science; Climate Sciences; Environmental Law; Political Science